The Importance of Da'wa Ethics in Social Media: A Quranic Perspective - Hakim, Lukman (Institut Agama Islam Negeri (IAIN) Keiri, 2023)
Technological advances that continue to develop make information accessible and consumed by the public quickly through social media. However, the impact of the use of social media needs to be considered by various groups of people, including Muslims. Social media can also be used as a medium of da'wah that influences society, especially Muslims, to always do good things according to the Qur'an and Hadith guidelines. This study aimed to explore the value of Islamic teachings from the Quran and Hadith, which can be used as the ethics of da’wa on social media. This study used qualitative method and took the form of a literature review. The main data sources used are various scientific literatures, both in the form of books and scientific journals, related to the discussion of ethical values in preaching on social media. While the secondary research data sources used are various scientific literature relevant to the core object of this research. The results of the study showed that there are various values in Islamic teachings that can be used as ethical values in da’wa on social media. Among these ethical values are: objective honesty based on facts; acting fairly and impartially in delivering lectures; and trying to apply the ethics of fairness and decency.